IAC 1711 citrandarin, tetraploid citranges and Flying Dragon trifoliate as potential graft-compatible rootstocks for Pera IAC sweet orange tree - Silva, Larissa Nunes; Vitória, Marina Ferreira [UNESP]; Moreira, Alécio Souza; Girardi, Eduardo Augusto; Stuchi, Eduardo Sanches (FapUNIFESP (SciELO), 2025)
ABSTRACT The Pera sweet orange tree is the most cultivated scion variety in Brazil, mainly grafted onto Rangpur lime rootstock. Despite its drought tolerance, Rangpur lime is susceptible to various citrus diseases. More recently, trifoliate orange and its hybrids have been used as alternative rootstocks, but most genotypes are graft-incompatible with Pera. In this study, we assessed the long-term performance of Pera IAC sweet orange, which is a pre-immunized clone against citrus tristeza virus, grafted onto 11 trifoliate orange-derived rootstocks, one somatic hybrid and the standard Rangpur lime. The experiment was installed in Bebedouro, SP, Brazil, in February 2011, in a rainfed regime. The design was completely randomized with 13 treatments, 10 replications and one tree in the plot. Changsha × English Large (IAC 1711) citrandarin rootstock conjugated the tallest trees, high cumulative yield, and good drought tolerance up to 2020, followed by Rangpur lime and tetraploid citranges. The Flying Dragon trifoliate orange and tetraploid Carrizo citrange (IAC 387) rootstocks induced the highest content of soluble solids and acidity in Pera oranges. At 9 years old, four citrandarins, a citradia and one somatic hybrid rootstocks were graft-incompatible with Pera IAC sweet orange. All scion/rootstocks’ combinations were affected by huanglongbing. The IAC 1711 citrandarin, tetraploids Troyer (IAC 385) and Carrizo (IAC 387) citranges and Flying Dragon trifoliate orange have potential as graft-compatible rootstocks of Pera IAC, but evaluations should continue in the long term. In addition, the later rootstock must be evaluated in irrigated high-density orchards aiming at competitive yields.